Green Tea Attenuates methomyl-Induced Cardiac Toxicity Through Modulating Oxidative Stress and Nuclear Factor kappa B Up- Regulation in Mice. Issue 1 (1st January 2021) - Manar R., Abdelkhalek; Omali Y., El-Khawaga; Rehab A., Elbnhawy; Hussam A., El-Gayar
ABSTRACT: Methomyl (ME) is a carbamate insecticide that is causes a change in biochemical parameters and affects the oxidative state in the body through the production of free radicals. Herbal medicines derived from plant extracts are useful in treating many diseases, as they are considered natural antioxidants that have a protective role against toxins. This study aimed to evaluate the ability of green tea extract (GTE) to treat ME-induced cardiac toxicity in experimental animals. The experimental animals were divided into five groups. Blood and tissue were collected to estimate the biochemical parameters. ME caused significantly elevated levels of AST, LDH, NF-κB, and malondialdehyde. While a significant decrease was observed in levels of superoxide dismutase, a decrease in glutathione and glutathione-S-transferase was observed. Alterations in these biochemical markers were referred to oxidative stress-induced cardiac damage. The administration of GTE at a concentration (1.5%) to the ME treated group caused the tested biochemical parameters to appear close to those of the control group. GTE alleviates ME-induced oxidative stress in female albino mice. A higher concentration of GTE {1.5%} appears to have a better therapeutic effect than a lower concentration of extract {0.75%} in cardiac toxicity ME.